Electron Densities and Temperatures in the Martian Ionosphere: MAVEN LPW Observations of Control by Crustal Fields. Issue 2 (17th February 2023) - Andrews, David J.; Stergiopoulou, Katerina; Andersson, Laila; Eriksson, Anders I. E.; Ergun, Robert E.; Pilinski, Marcin
Abstract: Mars Express and Mars Atmosphere and Volatile Evolution (MAVEN) observations have demonstrated the influence of Mars's spatially variable crustal magnetic fields upon the configuration of the plasma in the ionosphere. This influence furthermore leads to variations in ionospheric escape, conceivably in part through the modification of the plasma density and electron temperature in the upper ionosphere. In this study, we examine MAVEN Langmuir Probe and Waves data, finding a clear correspondence between the structure of the crustal fields and both the measured electron temperatures and densities, by first constructing an "average" profile from which departures can be quantified. Electron temperatures are shown to be lower in regions of strong crustal fields over a wide altitude range. We extend previous analyses to cover the nightside ionosphere, finding the same effects present to a lesser degree, in contrast to previous studies where the opposite relationship was found between densities and crustal fields. We further determine the altitude range over which this coupling between both plasma density (and temperature) and crustal fields is effective and use measurements made by MAVEN in the solar wind to explore the dependence of this crustal field control on the coupling to the solar wind and the interplanetary magnetic field (IMF). Based on this, there is some suggestion that variations in the solar wind dynamic pressure are associated with modulation of the effects of the crustal fields on plasma density, whereas the strength of the IMF modulates the crustal fields effects on both electron densities and temperatures. Plain Language Summary: Mars's atmosphere is exposed to ultra‐violet light from the Sun, forming a layer of plasma at high altitudes around the planet. This plasma layer, termed the ionosphere, is strongly affected in terms of its density and temperature, both by external factors like the solar wind and the interplanetary magnetic field (IMF), and internal factors, like Mars's crustal magnetic field. Here, we study how effective the crustal magnetic fields are at shaping the ionosphere in both density and temperature, by first determining the average structure of the ionosphere, and then examining departures from this average. We find that plasma densities are elevated and temperatures reduced in regions where the crustal field is stronger. We also find the same effect on the nightside. This result is in apparent opposition to previous related studies, now based on a much larger data set, which we suggest may be the result of poor seasonal sampling in earlier studies. We further investigate how this crustal field control varies with the solar wind and IMF, and see evidence for weak modulation according to both the dynamic pressure exerted by the solar wind, and the strength of the IMF. Key Points: We present a statistical analysis of Mars Atmosphere and Volatile Evolution Langmuir Probe and Wave densities and temperatures at Mars Densities are elevated and temperatures reduced in strong crustal field regions, on both the dayside and nightside Variations in the driving solar wind conditions are able to affect these correlations to a modest degree